Degradable magnesium metal artificial lamina

By using high-purity magnesium alloy and biodegradable magnesium metal artificial vertebral lamina with alloy element regulation, the biocompatibility and mechanical mismatch of existing metal implant devices have been solved, achieving a match between the biocompatibility and mechanical properties of magnesium alloy implant devices, and avoiding stress shielding and long-term implantation risks.

CN115770128BActive Publication Date: 2026-11-06SHANGHAI CHANGZHENG HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211453545.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-21
Publication Date
2026-11-06
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

Existing metal orthopedic implants, such as those made of titanium alloy and stainless steel, suffer from poor biocompatibility, mismatched elastic modulus, and non-degradability, leading to stress shielding and medical risks and economic burdens associated with long-term implantation.

Method used

Using high-purity magnesium alloy materials, a biodegradable magnesium metal artificial vertebral lamina is prepared by adding alloying elements with low electrode potential. Combined with clamping components and connectors, the size of the clamping cavity can be adjusted to accommodate vertebrae of different sizes, and the degradation rate is matched with bone growth.

Benefits of technology

This achieves a balance between the biocompatibility and mechanical properties of magnesium alloy implants, avoids stress shielding, and allows for gradual degradation without the need for secondary surgery, thus reducing medical risks and economic burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115770128B_ABST
    Figure CN115770128B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of medical devices, and particularly relates to a degradable magnesium metal artificial lamina. The application provides a degradable magnesium metal artificial lamina, which comprises a fixing plate, a connecting piece and a clamping assembly, and the fixing plate, the connecting piece and the clamping assembly are all prepared from degradable magnesium. Compared with conventional materials, the degradable magnesium metal is more close to human bones in performance, avoids stress shielding, accompanies the healing of a bone defect site, and gradually degrades the degradable magnesium metal artificial lamina, so that the degradable magnesium metal artificial lamina can realize the fixation of the bone defect and avoid the medical risks caused by long-term implantation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical device technology, specifically relating to a biodegradable magnesium metal artificial vertebral plate. Background Technology

[0002] In recent years, various types of bone plates have demonstrated advantages such as reliable fixation and good alignment in the clinical treatment of rib and clavicle fractures, gradually replacing traditional treatments such as chest bandage compression or traction fixation. The metal materials used in these implants mainly include medical-grade stainless steel and titanium alloys. Titanium alloys, with their low specific gravity, high strength, low elastic modulus, and ease of processing, have become a relatively ideal functional structural material for surgical implants. However, the complex internal environment of the human body can cause corrosion of metal materials, leading to the release of toxic elements and reduced biocompatibility. Secondly, the significant difference in elastic modulus between metal materials and human bone tissue can easily create a stress shielding effect, hindering the growth and remodeling of new bone and even leading to secondary fractures. Thirdly, currently used medical metal materials are all non-degradable; after the implant's service life in the body expires, it must be removed through a second surgery, increasing patient suffering and medical expenses. Therefore, researchers are committed to finding metal materials with better biocompatibility, closer mechanical properties to human bone, and biodegradability.

[0003] Currently, orthopedic implants made of titanium alloys, stainless steel, and cobalt-based alloys are the most commonly used in clinical practice. These materials offer stable fixation and excellent biocompatibility, but also have drawbacks such as high elastic modulus, high density, and non-biodegradability. In recent years, the application prospects of biodegradable magnesium alloys in absorbable orthopedic implants have attracted widespread attention from researchers worldwide. Summary of the Invention

[0004] This invention is based on the inventor's discoveries and understanding of the following facts and problems:

[0005] Magnesium alloys are absorbable implantable materials that offer superior mechanical properties and bioactivity compared to existing absorbable materials. Compared to biomedical active titanium alloys, magnesium alloys exhibit excellent biodegradability. Furthermore, titanium alloys are expensive, while my country is a major magnesium producer with abundant magnesium ore reserves. Magnesium alloys are significantly cheaper than titanium alloys and biodegradable polymers, giving magnesium alloy implants a substantial price advantage and significantly reducing the financial burden on patients.

[0006] However, magnesium alloys have poor corrosion resistance and degrade too quickly in the human body, making it difficult to achieve the required "service life" for implants and easily leading to a significant reduction in mechanical strength in the early stages of fixation.

[0007] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention propose a biodegradable magnesium metal artificial vertebral laminar plate, comprising a fixation plate, connectors, and clamping components, all of which are made of biodegradable magnesium metal. By increasing the purity of the magnesium-based material or further adding alloying elements with lower electrode potentials to high-purity magnesium metal, this invention achieves the goal of reducing the degradation rate of the magnesium-based material. Furthermore, the magnesium ions generated during the degradation of the magnesium-based material, along with other ions essential for the growth of human bone tissue, work together to effectively promote bone regeneration. This delays magnesium degradation while accelerating bone regeneration, allowing the degradation rate of the artificial vertebral body to be well matched with bone growth. Compared to conventional materials, biodegradable magnesium metal is closer to human bone, avoiding stress shielding. As the bone defect heals, the biodegradable magnesium metal artificial vertebral plate gradually degrades, achieving fixation of the bone defect while avoiding the medical risks associated with long-term implantation.

[0008] A biodegradable magnesium metal artificial vertebral plate according to an embodiment of the present invention includes a fixing plate, a connector and a clamping assembly;

[0009] A fixing plate, the fixing plate comprising a main body and two mounting portions, the two mounting portions being respectively arranged on opposite sides of the main body along a first direction;

[0010] A connector, which passes through the mounting portion and is adapted to connect to the human vertebral lamina;

[0011] A clamping assembly includes two clamping members, which are respectively arranged on both sides of the main body along a second direction and define a clamping cavity. The clamping cavity is used to clamp a human vertebral lamina. At least one of the two clamping members is adjustable in position relative to the main body along the second direction. Any two of the first direction, the second direction and the thickness direction of the main body are orthogonal.

[0012] The fixing plate, connectors, and clamping components are all made of biodegradable magnesium metal.

[0013] The advantages and technical effects of the biodegradable magnesium metal artificial vertebral plate in this invention are as follows: 1. In this invention, since the position of at least one of the two clamping members relative to the main body along the second direction is adjustable, the size of the clamping cavity can be adjusted by changing the position of the clamping members, thereby enabling the artificial vertebral plate to clamp and lock vertebrae of different specifications, expanding the applicability of the artificial vertebral plate; 2. In this invention, the artificial vertebral plate is made of biodegradable magnesium metal. Compared with conventional materials, biodegradable magnesium metal is closer to human bone, avoiding stress shielding. As the bone defect heals, the biodegradable magnesium metal artificial vertebral plate gradually degrades, achieving fixation of bone defects while avoiding the medical risks associated with long-term implantation.

[0014] In some embodiments, the concentration of a single impurity element in the degraded magnesium metal does not exceed 80 ppm, and the total impurity content is ≤0.01 wt%.

[0015] In some embodiments, the biodegradable magnesium metal includes at least one of high-purity metallic magnesium or high-purity magnesium-based alloys.

[0016] In some embodiments, the magnesium content in the high-purity metallic magnesium is ≥99.99 wt%.

[0017] In some embodiments, the high-purity magnesium-based alloy includes at least one of a magnesium alloy using commercially available grade composition, a binary alloy magnesium alloy, and a ternary alloy magnesium alloy.

[0018] The binary alloy system magnesium alloy includes at least one of Mg-Zn, Mg-Mn, Mg-Ca, Mg-Sr, and Mg-Re; wherein the content of rare earth elements Zn, Mn, Ca, Sr, and Re is 0.05 to 3.5 wt%.

[0019] The ternary alloy system magnesium alloy includes at least one of Mg-Zn-Ca, Mg-Zn-Zr, Mg-Zn-Mn, Mg-Re-Ca, and Mg-Re-Mn; wherein the content of Zn, Ca, and Mn elements is 0.05 to 3.5 wt%, and the content of Zr and Re rare earth elements is 0.03 to 1.5 wt%.

[0020] In some embodiments, the two clamping members are connected, and the position of both clamping members relative to the body is adjustable along the second direction.

[0021] In some embodiments, both clamping members include connected adjustment sections and locking sections. One adjustment section is provided with a first rack, and the other adjustment section is provided with a second rack. The first rack has a plurality of first locking teeth arranged along the second direction, and the second rack has a plurality of second locking teeth arranged along the second direction. The first locking teeth at different positions can elastically engage with the second locking teeth at different positions. The two locking sections define the clamping cavity.

[0022] In some embodiments, the main body is provided with an adjustment channel that extends through the main body along the second direction. Both clamping members include connected adjustment sections and snap-fit ​​sections. At least one of the two adjustment sections extends into the adjustment channel and is positionally adjustable relative to the adjustment channel along the second direction. The two snap-fit ​​sections define the clamping cavity.

[0023] In some embodiments, the fixing plate further includes a protrusion located on one side of the body thickness direction, the protrusion being used to insert into the cross-section of the vertebral plate.

[0024] In some embodiments, the bone contact surface of the protrusion is provided with a trabecular structure and / or a bone inlet hole.

[0025] In some embodiments, each of the mounting portions includes at least two lugs, the two lugs being arranged at a distance along the second direction and defining an opening groove, the lugs being provided with mounting holes, and the connector passing through the mounting holes;

[0026] And / or, a bending groove is provided at the connection position between the mounting part and the main body, and the bending groove extends along the first direction;

[0027] And / or, the main body is provided with a bone graft chamber.

[0028] In some embodiments, the mounting part is provided with a mounting hole, the connector is threadedly engaged with the mounting hole, the mounting hole is provided with a locking ring groove, and the outer peripheral wall of the connector is provided with a locking boss, which can be screwed into the locking ring groove.

[0029] In some embodiments, the front end of the locking boss is provided with a guide bevel so as to be screwed into the locking ring groove;

[0030] And / or, there are multiple locking bosses, and the multiple locking bosses are arranged at circumferential intervals along the locking ring groove. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of an artificial vertebral lamina according to an embodiment of the present invention;

[0032] Figure 2 This is an exploded view of the artificial vertebral lamina according to an embodiment of the present invention;

[0033] Figure 3 This is an internal schematic diagram of the artificial vertebral lamina before clamping, according to an embodiment of the present invention.

[0034] Figure 4 This is an internal schematic diagram of the artificial vertebral lamina after clamping according to an embodiment of the present invention;

[0035] Figure 5 This is a schematic diagram of the fixation plate of the artificial vertebral lamina according to an embodiment of the present invention;

[0036] Figure 6 This is a schematic diagram of the clamping component of the artificial vertebral lamina according to an embodiment of the present invention;

[0037] Figure 7 This is a schematic diagram of the connector of the artificial vertebral lamina according to an embodiment of the present invention;

[0038] Figure 8 This is a schematic diagram of the installation of the connector of the artificial vertebral lamina according to an embodiment of the present invention;

[0039] Figure 9 This is a schematic diagram illustrating the assembly effect of the biodegradable magnesium lamina replantation fixation plate prepared in Example 1.

[0040] Figure 10 These are scanning electron microscope images of the high-purity magnesium metal artificial vertebral lamina prepared in Example 1 after 6 months of in vitro degradation;

[0041] Figure 11 This is a scanning electron microscope image of the high-purity Mg-2.0Ca alloy artificial vertebral lamina prepared in Example 3 after 6 months of in vitro degradation;

[0042] Figure 12 This is a scanning electron microscope image of the high-purity Mg-3.0Zn-0.8Zr alloy artificial vertebral lamina prepared in Example 4 after 6 months of in vitro degradation. Detailed Implementation

[0043] Embodiments of the present invention are described in detail below, with examples of the embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0044] A biodegradable magnesium metal artificial vertebral plate according to an embodiment of the present invention includes a fixing plate, a connector and a clamping assembly;

[0045] The fixing plate includes a main body and two mounting parts, which are respectively arranged on opposite sides of the main body along a first direction;

[0046] A connector, which passes through the mounting part and is adapted to connect with the human vertebral lamina;

[0047] The clamping assembly includes two clamping members, which are respectively arranged on both sides of the main body along a second direction and define a clamping cavity. The clamping cavity is used to clamp the human vertebral lamina. The position of at least one of the two clamping members relative to the main body along the second direction is adjustable. Any two of the first direction, the second direction and the thickness direction of the main body are orthogonal.

[0048] The fixing plate, connectors, and clamping components are all made of biodegradable magnesium metal.

[0049] The biodegradable magnesium metal artificial vertebral plate of this invention has an adjustable position of at least one of the two clamping members relative to the main body along the second direction. This allows the size of the clamping cavity to be adjusted by changing the position of the clamping members, thereby enabling the artificial vertebral plate to clamp and lock vertebrae of different sizes, expanding the applicability of the artificial vertebral plate. In this invention, the artificial vertebral plate is made of biodegradable magnesium metal, which is closer to human bone than conventional materials, avoiding stress shielding. As the bone defect heals, the biodegradable magnesium metal artificial vertebral plate gradually degrades, achieving fixation of the bone defect while avoiding the medical risks associated with long-term implantation.

[0050] In some embodiments, preferably, the concentration of a single impurity element does not exceed 80 ppm, and the total impurity content is ≤0.01 wt%. More preferably, the biodegradable magnesium metal includes at least one of high-purity metallic magnesium or high-purity magnesium-based alloys. Even more preferably, the magnesium content in the high-purity metallic magnesium is ≥99.99 wt%. Even more preferably, the Fe concentration in the biodegradable magnesium metal does not exceed 80 ppm.

[0051] In this embodiment of the invention, the content of impurities in the biodegradable magnesium metal is limited, the type of biodegradable magnesium metal is preferred, and the content of added elements in the high-purity magnesium-based alloy is limited. Specifically, the iron content is limited to ≤80 ppm, as a high iron content will accelerate the corrosion degradation rate of the product. Impurity content not only significantly affects the corrosion behavior of magnesium, but the second phase formed by impurity atoms can also form corrosion microcouples with the magnesium matrix, accelerating matrix corrosion. Typically, the impurity content in magnesium metal is around 0.1% to 0.8%. In this embodiment of the invention, using biodegradable magnesium metal with low impurity content, compared to ordinary purity magnesium metal with higher impurity content, can reduce the degradation rate by 2-8 times, minimizing the side effects of implanting a biodegradable magnesium metal artificial vertebral lamina into the human body and ensuring the implantation effect.

[0052] In some embodiments, preferably, the high-purity magnesium-based alloy includes at least one of magnesium alloys using commercially available grade compositions, binary alloys, and ternary alloys.

[0053] In some embodiments, the commercial grades include at least one of AZ31, AZ91, AM60, ZK60, and WE43. In these embodiments, the high-purity magnesium-based alloys used can employ the compositions of existing commercially available magnesium alloy grades.

[0054] In some embodiments, the binary alloy magnesium alloy includes at least one selected from Mg-Zn, Mg-Mn, Mg-Ca, Mg-Sr, and Mg-Re; wherein the content of rare earth elements Zn, Mn, Ca, Sr, and Re is 0.05–3.5 wt%. In this embodiment of the invention, by limiting the content of alloying elements in the binary alloy, the content of the second phase formed by magnesium and alloying elements can be controlled, effectively improving the mechanical properties of the magnesium alloy while controlling the degradation rate of the alloy. This achieves a good match between the mechanical properties of the magnesium alloy, the degradation rate, and bone tissue recovery.

[0055] In some embodiments, the ternary alloy magnesium alloy includes at least one selected from Mg-Zn-Ca, Mg-Zn-Zr, Mg-Zn-Mn, Mg-Re-Ca, and Mg-Re-Mn; wherein the content of Zn, Ca, and Mn elements is 0.05–3.5 wt%, and the content of Zr and Re rare earth elements is 0.03–1.5 wt%. In this embodiment, by controlling the content of alloying elements in the magnesium alloy, the content of the second phase formed by magnesium and alloying elements and the content of free elemental phases are controlled, thereby achieving regulation of the corrosion degradation rate of the magnesium alloy. Furthermore, the free elemental phase can improve the mechanical properties of the magnesium alloy, but excessive free elemental phases can exacerbate galvanic corrosion, which is detrimental to the regulation of the product degradation rate. This embodiment achieves a good match between the mechanical properties of the magnesium alloy, the degradation rate, and bone tissue recovery.

[0056] This invention also provides a method for processing biodegradable magnesium metal, comprising the following steps:

[0057] (1) Degradable magnesium metal is melted in a vacuum induction furnace and then cast in a vacuum environment to obtain an ingot;

[0058] (2) Treat the ingot obtained in step (1) at 240-400℃ for 1-5 hours and then let it cool naturally to room temperature;

[0059] (3) Remove the oxide layer on the surface of the ingot obtained in step (2) and use an extrusion process to obtain magnesium metal rods for artificial vertebral plates.

[0060] The biodegradable magnesium metal processing method provided in this invention uses an extrusion process to process magnesium metal. The magnesium metal produced by this forming process has the characteristics of dense structure and fine grains, and the prepared magnesium metal has high quality and is more suitable for use in the preparation of artificial vertebral plates.

[0061] In some embodiments, preferably, when the degradable magnesium metal is a high-purity magnesium-based alloy, the method further includes step (4): heating the bar obtained in step (3) to 320–450°C in a vacuum heat treatment furnace for 7–18 hours, and then quenching it; after quenching, heating the bar to 140–250°C in a heat treatment furnace for 5–24 hours, and then naturally cooling it to room temperature. More preferably, the vacuum degree in the vacuum heat treatment furnace is ≤8×10⁻⁶. -3 Pa.

[0062] In some embodiments, preferably, when the biodegradable magnesium metal is high-purity magnesium metal, the processing method of the biodegradable magnesium metal is as follows: 1. Melting in a vacuum induction melting furnace and then casting to obtain an ingot; 2. Treating the obtained ingot at a temperature of 280-350℃ for 1-3 hours, and then naturally cooling to room temperature; 3. Removing the surface oxide layer, heating to 350℃, holding at that temperature for 0.5 hours, and then completing the extrusion process using an extruder, ensuring an extrusion ratio of 32-80:1, to obtain high-purity magnesium metal rods for spinal lamina reimplantation fixation products. The high-purity magnesium metal rods obtained in the embodiments of the present invention have a tensile strength of 140-210 MPa, an elongation after fracture of 15-20%, a magnesium element content ≥99.99 wt% in the high-purity magnesium metal, a single impurity content not exceeding 80 ppm, and a total impurity content ≤0.01 wt%.

[0063] In some embodiments, preferably, when the biodegradable magnesium metal is a high-purity magnesium alloy using commercially available grades, the processing method for the biodegradable magnesium metal is as follows: 1. Melting in a vacuum induction melting furnace and then casting to obtain an ingot; 2. Treating the obtained ingot at 250-400℃ for 1.2-5 hours, and then naturally cooling to room temperature; 3. Removing the surface oxide layer, heating to 380-420℃, holding at that temperature for 0.5 hours, and then completing the extrusion process using an extruder, ensuring an extrusion ratio of 16-80:1, to obtain high-purity magnesium alloy extruded bars; 4. Extruding the high-purity magnesium alloy extruded bars under a vacuum degree ≤8×10 -3 The rods are heated to 380-450℃ in a high-vacuum heat treatment furnace for 7-12 hours, followed by quenching. After quenching, the rods are heated to 140-210℃ in a heat treatment furnace for 5-24 hours, and then naturally cooled to room temperature to obtain high-purity magnesium alloy rods with a commercially available grade composition for artificial vertebral plates. The high-purity magnesium alloy rods with a commercially available grade composition prepared in this embodiment have a tensile strength of 230-380 MPa and an elongation after fracture of 18-22%. The magnesium alloy prepared using the above process has a more uniform composition, a grain size between 1 and 50 μm, significantly improved mechanical properties, and a much lower degradation rate compared to commercially available magnesium alloys of the same composition.

[0064] In some embodiments, preferably, when the biodegradable magnesium metal is a binary high-purity magnesium alloy, the processing method of the biodegradable magnesium metal is as follows: 1. Melting in a vacuum induction melting furnace and then casting to obtain an ingot; 2. Treating the obtained ingot at 240-350℃ for 1.5-5 hours, and then naturally cooling to room temperature; 3. Removing the surface oxide layer, heating to 400-450℃, holding at that temperature for 0.5 hours, and then completing the extrusion process using an extruder, ensuring an extrusion ratio of 32-80:1, to obtain a binary high-purity magnesium alloy extruded bar; 4. Extruding the binary high-purity magnesium alloy extruded bar under a vacuum degree ≤8×10 -3 The rods are heated to 320-420℃ in a high-vacuum heat treatment furnace for 7-12 hours, followed by quenching. After quenching, the rods are heated to 150-220℃ in a heat treatment furnace for 6-24 hours, and then naturally cooled to room temperature to obtain binary high-purity magnesium alloy rods for artificial conical plates. In this embodiment, the tensile strength of the obtained binary high-purity magnesium alloy rods is 280-350 MPa, and the elongation after fracture is 11-24%. The magnesium alloy prepared by the above process has a more uniform composition, a grain size between 1 and 30 μm, significantly improved mechanical properties, and a much lower degradation rate compared to ordinary binary magnesium alloys of the same composition.

[0065] In some embodiments, preferably, when the biodegradable magnesium is a ternary high-purity magnesium alloy, the processing method of the biodegradable magnesium metal is as follows: 1. Melting in a vacuum induction melting furnace and then casting to obtain an ingot; 2. Treating the obtained ingot at a temperature of 250-380℃ for 2-5 hours, and then naturally cooling to room temperature; 3. Removing the surface oxide layer, heating to 420-450℃, holding at that temperature for 0.5 hours, and then completing the extrusion process using an extruder, ensuring an extrusion ratio of 32-80:1, to obtain ternary high-purity magnesium alloy extruded bars; 4. Extruding the ternary high-purity magnesium alloy extruded bars under a vacuum degree ≤8×10 -3 The rods are heated to 350-420℃ in a high-vacuum heat treatment furnace for 12-18 hours, followed by quenching. After quenching, the rods are heated to 170-250℃ in a heat treatment furnace for 6-24 hours, and then naturally cooled to room temperature to obtain ternary high-purity magnesium alloy rods for artificial conical plates. In this embodiment, the tensile strength of the obtained ternary high-purity magnesium alloy rods is 290-380 MPa, and the elongation after fracture is 17-25%. The magnesium alloy prepared by the above process has a more uniform composition, a grain size between 1 and 40 μm, significantly improved mechanical properties, and a much lower degradation rate compared to ordinary ternary magnesium alloys of the same composition.

[0066] like Figures 1 to 8As shown, the artificial vertebral lamina according to an embodiment of the present invention includes: a fixation plate 1, a connector 2, and a clamping assembly 3. The fixation plate 1 includes a main body 11 and two mounting portions 12, the two mounting portions 12 being aligned along a first direction (e.g., ...). Figure 1 The components (in the direction A) are respectively arranged on opposite sides of the main body 11. The connector 2 passes through the mounting part 12 and is adapted to connect with the human vertebral lamina. The clamping assembly 3 includes two clamping members 31, which are arranged along the second direction (e.g., direction A). Figure 1 The clamping elements 31 are arranged on both sides of the main body 11 in the second direction (B direction) and define a clamping cavity 32. The clamping cavity 32 is used to clamp the human vertebral lamina. The position of at least one of the clamping elements 31 relative to the main body 11 is adjustable along the second direction. Any two of the first direction, the second direction and the thickness direction of the main body 11 are orthogonal.

[0067] It is understood that the positions of both clamping members 31 relative to the main body 11 can be adjusted along the second direction, or one of the clamping members 31 can be adjusted along the second direction relative to the main body 11, while the other clamping member 31 is fixed relative to the main body 11. In embodiments of the present invention, the artificial vertebral plate adjusts the size of the clamping cavity 32 by changing the position of the clamping member 31, thereby enabling the artificial vertebral body to clamp vertebrae of different sizes.

[0068] According to an embodiment of the present invention, an artificial vertebral laminae can be placed on top of a missing vertebral laminae and then fixed by a connector 2. Furthermore, two clamping members 31 can be used to clamp the vertebrae, further improving the reliability of the artificial vertebral laminae connection. Additionally, since the position of the clamping members 31 relative to the main body 11 along the second direction is adjustable, the size of the clamping cavity 32 can be adjusted by changing the position of the clamping members 31, thereby allowing the artificial vertebral laminae to clamp and lock vertebrae of different sizes. Therefore, the artificial vertebral laminae of the present invention have a robust connection, are suitable for different patients, and expand the applicability of artificial vertebral laminae.

[0069] Optionally, such as Figures 1 to 4 As shown, two clamping members 31 are connected, and the position of both clamping members 31 relative to the main body 11 is adjustable along the second direction. It can be understood that the movable position of both clamping members 31 relative to the main body 11 expands the adjustment range of the clamping cavity 32 and broadens the application range of the artificial vertebral body. For example, the two clamping members 31 can be connected by a snap-fit ​​method or by a threaded connection. By changing their connection position, the size of the clamping cavity 32 can be adjusted, facilitating the manufacturing of the artificial vertebral plate and simplifying assembly.

[0070] Specifically, such as Figures 2 to 4 and Figure 6As shown, both clamping members 31 include connected adjusting sections 321 and engaging sections 322. One adjusting section 321 is provided with a first rack 3211, and the other adjusting section 321 is provided with a second rack 3212. The first rack 3211 has multiple first locking teeth 32111 arranged along a second direction, and the second rack 3212 has multiple second locking teeth 32121 arranged along the second direction. The first locking teeth 32111 at different positions can elastically engage with the second locking teeth 32121 at different positions. The two engaging sections 322 define the clamping cavity 32. It can be understood that both the first locking teeth 32111 and the second locking teeth 32121 can be of a reverse tooth structure. When the doctor moves the two clamping members 31 toward each other, the first locking tooth 3211 and the second locking tooth 3212 can slide relative to each other due to the elasticity of the first rack 3211 and the second rack 3212. After the clamping member 31 clamps onto the human vertebra, the first locking tooth 32111 and the second locking tooth 32121 engage with each other to lock the artificial vertebral laminae. In addition, since both the first locking tooth 32111 and the second locking tooth 32121 have a reverse tooth structure, the clamping member 31 can be prevented from retracting, thus improving the fixation effect of the artificial vertebral laminae.

[0071] For example, such as Figure 5 As shown, the snap-fit ​​section 322 can be a hook structure, and the snap-fit ​​section 322 can be integrally formed with the adjustment section 321, thereby facilitating the processing and manufacturing of the clamping part 31.

[0072] Optionally, such as Figure 2 and Figure 6 As shown, the main body 11 is provided with an adjustment channel 111, which extends through the main body 11 along a second direction. Both clamping members 31 include connected adjustment sections 321 and snap-fit ​​sections 322. At least one of the two adjustment sections 321 extends into the adjustment channel 111 and its position relative to the adjustment channel 111 along the second direction is adjustable. For example, in an embodiment of the present invention, one adjustment section 321 extends into the adjustment channel 111 from its first end, and the other adjustment section 321 extends into the adjustment channel 111 from its second end. Both adjustment sections 321 are adjustable in position relative to the adjustment channel 111. It is understood that because the adjustment section 321 is located within the adjustment channel 111 of the main body 11, the artificial vertebral plate structure is compact, and the movement of the adjustment section 321 during the adjustment of the clamping member 31 will not interfere with other areas of the human body, thus improving the reliability of the artificial vertebral plate.

[0073] In some embodiments, such as Figures 1 to 3As shown, the fixation plate 1 also includes a protrusion 13, which is located on one side of the body 11 in the thickness direction. The protrusion 13 is used to insert into the cross-section of the vertebral lamina. It can be understood that the body 11 covers the surface of the missing human vertebral lamina, and the protrusion 13 is inserted into the cross-section of the missing human vertebral lamina, thereby making the structure of the human vertebra more stable and improving the surgical outcome.

[0074] For example, such as Figures 1 to 3 As shown, the bone contact surface of the protrusion 13 is provided with a trabecular structure 131 and / or a bone elongation hole 132. It is understood that the surface of the protrusion 13 in contact with the human vertebra can be provided with a porous trabecular structure, or with a geometric bone elongation hole 132, or the bone contact surface of the protrusion 13 can simultaneously provide a porous trabecular structure and a geometric bone elongation hole 132. In embodiments of the present invention, by configuring the protrusion 13 with the above-described structure, the artificial vertebral laminar plate can achieve better fusion with the human vertebra, improving the stability of the artificial vertebral laminar plate connection.

[0075] In some embodiments, such as Figure 1 , Figure 2 and Figure 5 As shown, each mounting portion 12 includes at least two lugs 121, which are spaced apart along a second direction and define an opening slot 122. Each lug 121 has a mounting hole 1211 through which the connector 2 passes. It is understood that each mounting portion 12 includes multiple lugs 121 (two or more lugs 121). In this embodiment, there are two lugs 121, meaning that each of the two mounting portions 12 located on opposite sides of the main body 11 has two lugs 121. For example, when there are two or more lugs 121, an opening slot 122 is provided between each pair of adjacent lugs 121. The artificial vertebral plate of this embodiment allows for fine adjustment of the relative position or angle of each lug 121 by providing an opening slot 122 between two lugs 121.

[0076] Optionally, such as Figure 1 , Figure 2 and Figure 5 As shown, a bending groove 112 is provided at the connection position between the mounting part 12 and the main body 11. The bending groove 112 extends along a first direction. It can be understood that the bending groove 112 can be provided on both sides of the thickness direction of the main body 11. By providing the bending groove 112, the artificial vertebral plate of the embodiment of the present invention can facilitate the doctor to bend the mounting part 12, thereby allowing the mounting part 12 and the main body 11 to fully fit with the bone surface of the vertebra, improving the implantation effect of the artificial vertebral plate.

[0077] Optionally, such as Figure 1 , Figure 2 and Figure 5As shown, the main body 11 is provided with a bone graft chamber 113. It can be understood that the bone graft chamber 113 penetrates the main body 11 along its thickness direction, and the bone graft chamber 113 can extend along a second direction. In this embodiment of the invention, the artificial vertebral plate, by providing the bone graft chamber 113, facilitates the ingrowth of human bone into the bone graft chamber 113, thereby further improving the reliability of the connection between the artificial vertebral plate and the human vertebra.

[0078] In some embodiments, such as Figure 1 , Figure 7 and Figure 8 As shown, the connector 2 is threaded into the mounting hole 1211. The mounting hole 1211 has a locking ring groove 1212, and the outer peripheral wall of the connector 2 has a locking boss 221, which can be screwed into the locking ring groove 1212. Specifically, the connector 2 includes a connected screw portion 21 and a nut portion 22. The screw portion 21 is threaded into the mounting hole 1211, and the locking boss 221 is located on the side of the nut portion 22 adjacent to the screw portion 21. By providing the locking ring groove 1212 and the locking boss 221, the artificial vertebral plate of this embodiment can improve the firmness of the connection between the connector 2 and the mounting hole 1211 and reduce the probability of the connector 2 retracting.

[0079] Specifically, such as Figure 7 and Figure 8 As shown, the front end of the locking boss 221 is provided with a guide slope 2211 so as to be screwed into the locking ring groove 1212. It can be understood that when the connector 2 is screwed into the mounting hole 1211, the guide slope 2211 is provided in the forward direction of the locking boss 221. When the locking boss 221 is screwed into the locking ring groove 1212, the guide slope 2211 first contacts the locking ring groove 1212, thereby guiding the movement of the locking boss 221 so that the locking boss 221 can be smoothly screwed into the locking ring groove 1212.

[0080] Optionally, such as Figure 7 and Figure 8 As shown, there are multiple locking bosses 221, which are arranged at intervals along the circumference of the locking ring groove 1212. This can further improve the firmness of the connection between the connector 2 and the mounting hole 1211, reduce the probability of the connector 2 retracting, and reduce the risk of the connector 2 detaching from the fixing plate 1.

[0081] The present invention will now be described in detail with reference to the embodiments.

[0082] Example 1

[0083] A biodegradable magnesium metal artificial vertebral lamina was prepared using high-purity metallic magnesium. The processing steps for high-purity metallic magnesium are as follows:

[0084] (1) Magnesium metal with a single impurity element concentration not exceeding 80 ppm and a total impurity content ≤0.01 wt% is used under a vacuum degree ≤8×10 -3 The melting is carried out in a vacuum induction furnace with a vacuum degree ≤8×10 Pa, and the melting is carried out in a vacuum degree ≤8×10 Pa. -3 Ingots are formed by pouring at a Pa environment;

[0085] (2) The obtained ingot was treated at 280℃ for 3 hours and then naturally cooled to room temperature;

[0086] (3) Remove the oxide layer on the surface of the ingot in step (2), heat it to 350°C, keep it at that temperature for 0.5 hours, and then use an extruder to complete the extrusion process, ensuring that the extrusion ratio is 32:1, to obtain high-purity magnesium metal rods for artificial conical plates.

[0087] In the pure magnesium rod prepared in Example 1, the magnesium content was ≥99.995wt%, the total impurity content was ≤0.005wt%, the tensile strength of the rod was 200MPa, and the elongation after fracture was 20%.

[0088] Artificial vertebral lamina were prepared using the above-mentioned high-purity magnesium rod material. The structure of the prepared artificial vertebral lamina is shown in the figure. Figure 1-8 .

[0089] 1. The artificial vertebral plate described above is used to fix the artificial bone defect. The adjustment segment 321 is inserted into the adjustment channel 111 in opposite directions, and the first locking tooth 32111 is locked in the initial state.

[0090] 2. When locking, press the two adjusting sections 321 inward. Due to the overall elasticity of the first rack 3211 and the second rack 3212, the adjusting sections can slide inward and lock, ultimately locking through the reverse teeth. Figure 6 As shown;

[0091] 3. Connector 2 cooperates with fixing plate 1 to achieve locking, such as... Figure 7 As shown;

[0092] Figure 9 This is a schematic diagram showing the completed assembly of the artificial vertebral lamina.

[0093] The aforementioned high-purity magnesium artificial vertebral lamina was subjected to in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in the simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 43%, with a degradation rate of 0.048 mm / year. All components of the artificial vertebral lamina exhibited a uniform corrosion state. Scanning electron micrographs of the surface are shown below. Figure 10As shown, the first rack 3211 and the second rack 3212 of the artificial vertebral lamina fit well, but the tips of the first rack 3211 and the second rack 3212 show partial degradation and loss. The connection between the connector 2 and the fixing plate 1 is quite loose. After 12 months of degradation, the overall weight loss reached 90%, the degradation rate was 0.035 mm / year, the artificial vertebral lamina was basically completely disintegrated, and a small amount of high-purity magnesium metal remained.

[0094] Experimental Example 2

[0095] A biodegradable magnesium metal artificial vertebral plate with the same structure as in Example 1 was prepared using a high-purity magnesium alloy with the commercial grade WE43. The processing procedure for the magnesium alloy was as follows:

[0096] (1) Using high-purity magnesium and high-purity elemental yttrium, neodymium, and zirconium as raw materials, under a vacuum degree ≤8×10 -3 The melting is carried out in a vacuum induction furnace with a vacuum degree ≤8×10 Pa, and the melting is carried out in a vacuum degree ≤8×10 Pa. -3 Ingots are formed by pouring at a Pa environment;

[0097] (2) The resulting ingot was treated at 400℃ for 1.2 hours and then allowed to cool naturally to room temperature;

[0098] (3) Remove the oxide layer on the surface of the ingot in step (2), heat it to 420°C, keep it at that temperature for 0.5 hours, and then use an extruder to complete the extrusion process, ensuring that the extrusion ratio is 80:1, to obtain commercial high-purity magnesium alloy extruded bars;

[0099] (4) The high-purity magnesium alloy extruded bar obtained in step (3) is subjected to a vacuum degree ≤8×10 -3 The material is heated to 380°C in a high-vacuum heat treatment furnace for 12 hours, and then quenched. After quenching, the material is heated to 210°C in a heat treatment furnace for 5 hours, and then naturally cooled to room temperature to obtain commercial high-purity magnesium alloy rods for biodegradable magnesium metal artificial vertebral plates.

[0100] In the high-purity magnesium alloy bar prepared in Example 2, the composition of the high-purity magnesium alloy is as follows: the mass content of magnesium is ≥93.24%, the mass content of yttrium is 4.0%, the mass content of neodymium is 2.25%, the mass content of zirconium is 0.5%, the mass content of other total impurity elements is ≤0.01%, the tensile strength is 380 MPa, and the elongation after fracture is 22%.

[0101] The aforementioned high-purity magnesium alloy artificial vertebral lamina, using the commercially available grade WE43, underwent in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in the simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 50%, with a degradation rate of 0.18 mm / year. The components of the artificial vertebral lamina exhibited uniform corrosion with pitting corrosion at the joints. The first and second racks 3211 and 3212 of the artificial vertebral lamina showed relatively good fit, with no degradation or loss of the tooth tips. However, pitting corrosion appeared on the tightly contacting surfaces, and the connection between connector 2 and fixing plate 1 showed slight looseness. After 12 months of degradation, the overall weight loss reached 92%, with a degradation rate of 0.12 mm / year. The artificial vertebral lamina was essentially completely disintegrated, with a small amount of magnesium alloy fragments and corrosion products remaining.

[0102] Example 3

[0103] A biodegradable magnesium metal artificial vertebral plate with the same structure as in Example 1 was prepared using a binary Mg-2.0Ca high-purity magnesium alloy. The processing procedure for the binary high-purity magnesium alloy is as follows:

[0104] (1) Mg-2.0Ca magnesium alloy raw material with a single impurity element concentration not exceeding 80ppm and a total impurity content ≤0.01wt% is used under a vacuum degree ≤8×10 -3 The melting is carried out in a vacuum induction furnace with a vacuum degree ≤8×10 Pa, and the melting is carried out in a vacuum degree ≤8×10 Pa. -3 Ingots are formed by pouring at a Pa environment;

[0105] (2) The obtained ingot was treated at 240℃ for 5 hours and then naturally cooled to room temperature;

[0106] (3) Remove the oxide layer on the surface of the ingot in step (2), heat it to 450°C, keep it at that temperature for 0.5 hours, and then use an extruder to complete the extrusion process, ensuring that the extrusion ratio is 32:1, to obtain binary high-purity magnesium alloy extruded bar stock.

[0107] (4) The binary high-purity magnesium alloy extrusion bar obtained in step (3) is subjected to a vacuum degree ≤8×10 -3 The material is heated to 420°C in a high-vacuum heat treatment furnace for 7 hours, and then quenched. After quenching, the material is heated to 220°C in a heat treatment furnace for 6 hours, and then naturally cooled to room temperature to obtain a binary high-purity magnesium alloy rod for use in biodegradable magnesium metal artificial conical plates.

[0108] The high-purity binary Mg-2.0Ca magnesium alloy prepared in Example 3 has the following composition: magnesium content ≥97.99%, calcium content 2.0%, other total impurity content ≤0.01%, and the tensile strength of the binary high-purity magnesium alloy bar is 350 MPa, with an elongation after fracture of 24%.

[0109] Artificial vertebral lamina are fabricated using a high-purity binary Mg-2.0Ca alloy.

[0110] The high-purity binary Mg-2.0Ca alloy artificial vertebral lamina was subjected to in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in the simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 48%, with a degradation rate of 0.15 mm / year. The components of the artificial vertebral lamina exhibited uniform corrosion, with pitting corrosion appearing at the locking points of the fixing plate 1 and connector 2. Scanning electron micrographs of the surface are shown below. Figure 11 As shown, the first rack 3211 and the second rack 3212 of the artificial vertebral lamina fit relatively well, and the tips of the first rack 3211 and the second rack 3212 did not degrade or become missing. The connector 2 and the fixing plate 1 were slightly loose. After 12 months of degradation, the overall weight loss reached 94%, the degradation rate was 0.13 mm / year, the artificial vertebral lamina was basically completely disintegrated, and a small amount of magnesium alloy fragments and corrosion products remained.

[0111] Example 4

[0112] A biodegradable magnesium metal artificial vertebral plate with the same structure as in Example 1 was prepared using a ternary Mg-3.0Zn-0.8Zr high-purity magnesium alloy. The processing procedure for the ternary high-purity magnesium alloy is as follows:

[0113] (1) Mg-3.0Zn-0.8Zr magnesium alloy raw material with a single impurity element concentration not exceeding 80ppm and a total impurity content ≤0.01wt% is used under a vacuum degree ≤8×10 -3 The melting is carried out in a vacuum induction furnace with a vacuum degree ≤8×10 Pa, and the melting is carried out in a vacuum degree ≤8×10 Pa. -3 Ingots are formed by pouring at a Pa environment;

[0114] (2) The above-mentioned ingots were treated at 380°C for 2 hours and then naturally cooled to room temperature;

[0115] (3) Remove the oxide layer on the surface of the ingot in step (2), heat it to 450°C, keep it at that temperature for 0.5 hours, and then use an extruder to complete the extrusion process, ensuring that the extrusion ratio is 80:1, to obtain ternary high-purity magnesium alloy extruded bar stock.

[0116] (4) The ternary high-purity magnesium alloy extrusion bar obtained in step (3) is subjected to a vacuum degree ≤8×10 -3 The material is heated to 420°C in a high-vacuum heat treatment furnace for 12 hours, and then quenched. After quenching, the material is heated to 170°C in a heat treatment furnace for 24 hours, and then naturally cooled to room temperature to obtain ternary high-purity magnesium alloy rods for biodegradable magnesium metal artificial conical plates.

[0117] The high-purity ternary Mg-3.0Zn-0.8Zr alloy prepared in Example 4 has the following composition: magnesium content ≥96.19%, zinc content 3.0%, zirconium content 0.8%, and other total impurity content ≤0.01%. The tensile strength of the ternary high-purity magnesium alloy bar is 380 MPa, and the elongation after fracture is 25%.

[0118] Artificial vertebral lamina are fabricated using a high-purity ternary Mg-3.0Zn-0.8Zr alloy.

[0119] The aforementioned high-purity ternary Mg-3.0Zn-0.8Zr alloy biodegradable magnesium metal artificial vertebral lamina was subjected to in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 55%, with a degradation rate of 0.25 mm / year. All components of the artificial vertebral lamina exhibited uniform corrosion, with pitting corrosion appearing at the locking points of the fixing plate 1 and connector 2. Surface scanning electron microscope images are shown below. Figure 12 As shown, the first rack 3211 and the second rack 3212 of the artificial vertebral lamina fit relatively well. However, the tips of the first rack 3211 and the second rack 3212 degraded and were missing, with a loss of 46% of the tooth tip volume. The connector 2 and the fixing plate 1 were slightly loose. After 12 months of degradation, the overall weight loss reached 92%, with a degradation rate of 0.21 mm / year. The artificial vertebral lamina was basically completely disintegrated, with a small amount of magnesium alloy fragments and corrosion products remaining.

[0120] Comparative Example 1

[0121] It is the same as the artificial vertebral lamina in Example 1, except that the impurity content of the magnesium metal used is different.

[0122] The industrial-grade pure magnesium rod prepared in Comparative Example 1 has a magnesium content of 99.5% by mass, a total impurity element content of 0.5% by mass, an Fe content of 0.1%, a tensile strength of 145 MPa, and an elongation after fracture of 16%.

[0123] The in vitro degradation experiment was conducted using the same method as in Example 1. The pure magnesium metal artificial vertebral lamina was subjected to in vitro degradation in simulated body fluid at 37°C. After 6 months of degradation in the simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 74%, with a degradation rate of 0.084 mm / year. The components of the artificial vertebral lamina exhibited obvious pitting corrosion. The first rack 3211 and the second rack 3212 of the artificial vertebral lamina completely loosened, and approximately 60% of the tips of the first rack 3211 and the second rack 3212 were degraded and missing, with obvious corrosion pits appearing on the rack sections. The connector 2 and the fixing plate 1 also completely loosened. After 12 months of degradation, the overall weight loss reached 95%, with a degradation rate of 0.037 mm / year. The artificial vertebral lamina was essentially completely disintegrated, with a small amount of magnesium metal residue remaining.

[0124] Comparative Example 2

[0125] The artificial vertebral lamina is the same as that in Example 2, except that the high-purity magnesium alloy used is commercially available grade WE43.

[0126] The high-purity magnesium alloy prepared in Comparative Example 2 has the following composition: magnesium content of 92.7%, yttrium content of 3.8%, neodymium content of 2.2%, zirconium content of 0.5%, and other total impurity element content of 0.8%, of which Fe content is 0.1%. The tensile strength of the bar is 330 MPa and the elongation after fracture is 17%.

[0127] The in vitro degradation experiment was conducted using the same method as in Example 2. A magnesium alloy artificial vertebral lamina with grade WE43 was used in a simulated body fluid at 37°C for in vitro degradation. After 6 months of degradation in the simulated body fluid, the artificial vertebral lamina showed a total weight loss of 68%, with a degradation rate of 0.24 mm / year. All components of the artificial vertebral lamina exhibited severe pitting corrosion. The first rack 3211 and the second rack 3212 of the artificial vertebral lamina completely loosened, and approximately 50% of the tips of the first rack 3211 and the second rack 3212 were degraded and missing. Obvious corrosion pits appeared on the rack sections, and the connector 2 and the fixing plate 1 completely loosened. After 12 months of degradation, the total weight loss reached 93%, with a degradation rate of 0.12 mm / year. The artificial vertebral lamina was essentially completely disintegrated, with a small amount of magnesium alloy fragments and corrosion products remaining.

[0128] Comparative Example 3

[0129] It is the same as the artificial vertebral lamina in Example 3, except that the impurity content of the Mg-2.0Ca magnesium alloy used is different.

[0130] The Mg-2.0Ca magnesium alloy prepared in Comparative Example 3 has a magnesium content of ≥97.2% by mass, a calcium content of 2.0% by mass, and a total impurity element content of 0.8%, of which the Fe content is 0.2%. The tensile strength is 260 MPa and the elongation after fracture is 15%.

[0131] The in vitro degradation experiment was conducted using the same method as in Example 3. The Mg-2.0Ca magnesium alloy artificial vertebral lamina was subjected to in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 72%, with a degradation rate of 0.23 mm / year. All components of the artificial vertebral lamina exhibited severe pitting corrosion. The first rack 3211 and the second rack 3212 of the artificial vertebral lamina completely loosened, and approximately 60% of the tips of the first rack 3211 and the second rack 3212 showed degradation and loss, with obvious corrosion pits appearing on the rack sections. The connector 2 and the fixing plate 1 also completely loosened. After 12 months of degradation, the overall weight loss reached 93%, with a degradation rate of 0.12 mm / year. The artificial vertebral lamina was essentially completely disintegrated, with a small amount of magnesium alloy fragments and corrosion products remaining.

[0132] Comparative Example 4

[0133] It is the same as the artificial vertebral plate in Example 4, except that the impurity content of the Mg-3.0Zn-0.8Zr magnesium alloy used is different.

[0134] The Mg-3.0Zn-0.8Zr magnesium alloy prepared in Comparative Example 4 contained 95.46% magnesium, 3.0% zinc, 0.8% zirconium, and 0.74% other total impurity elements, including 0.1% Fe. It had a tensile strength of 340 MPa and an elongation after fracture of 15%.

[0135] The in vitro degradation experiment was conducted using the same method as in Example 4. The Mg-3.0Zn-0.8Zr magnesium alloy artificial vertebral lamina was subjected to in vitro degradation experiments in simulated body fluid at 37°C. After 6 months of degradation in simulated body fluid, the artificial vertebral lamina showed an overall weight loss of 75%, with a degradation rate of 0.31 mm / year. All components of the artificial vertebral lamina exhibited severe pitting corrosion. The first rack 3211 and the second rack 3212 of the artificial vertebral lamina completely loosened, and approximately 80% of the tips of the first rack 3211 and the second rack 3212 were degraded and missing, with severe corrosion pits appearing on the rack sections. The connector 2 and the fixing plate 1 also completely loosened. After 12 months of degradation, the overall weight loss reached 98%, with a degradation rate of 0.23 mm / year. The artificial vertebral lamina was essentially completely disintegrated, with a small amount of magnesium alloy fragments and corrosion products remaining.

[0136] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0137] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.

Claims

1. A biodegradable magnesium metal artificial vertebral lamina, characterized in that, Includes a fixing plate, connectors, and clamping components; A fixing plate, the fixing plate comprising a main body and two mounting portions, the two mounting portions being respectively arranged on opposite sides of the main body along a first direction; A connector, which passes through the mounting portion and is adapted to connect to the human vertebral lamina; A clamping assembly includes two clamping members, which are respectively arranged on both sides of the main body along a second direction and define a clamping cavity for clamping a human vertebral lamina. At least one of the two clamping members is adjustable in position relative to the main body along the second direction, and any two of the first direction, the second direction, and the thickness direction of the main body are orthogonal. The fixing plate also includes a protrusion located on one side of the thickness direction of the main body and is used to insert into the cross-section of the vertebral lamina. The fixing plate, connectors, and clamping components are all made of biodegradable magnesium metal; The concentration of a single impurity element in the biodegradable magnesium metal does not exceed 80 ppm, the total impurity content is ≤0.01 wt%, and the concentration of Fe element in the biodegradable magnesium metal does not exceed 80 ppm.

2. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, The biodegradable magnesium metal includes at least one of high-purity metallic magnesium or high-purity magnesium-based alloys.

3. The biodegradable magnesium metal artificial vertebral lamina according to claim 2, characterized in that, The high-purity metallic magnesium contains ≥99.99 wt% magnesium.

4. The biodegradable magnesium metal artificial vertebral lamina according to claim 2, characterized in that, The high-purity magnesium-based alloy includes at least one of the following: magnesium alloys using commercially available grade compositions, binary alloy magnesium alloys, and ternary alloy magnesium alloys. The binary alloy system magnesium alloy includes at least one selected from Mg-Zn, Mg-Mn, Mg-Ca, Mg-Sr, and Mg-Re; wherein the content of rare earth elements Zn, Mn, Ca, Sr, and Re is 0.05~3.5 wt%. The ternary alloy system magnesium alloy includes at least one of Mg-Zn-Ca, Mg-Zn-Zr, Mg-Zn-Mn, Mg-Re-Ca, and Mg-Re-Mn; wherein the content of Zn, Ca, and Mn elements is 0.05~3.5 wt%, and the content of Zr and Re rare earth elements is 0.03~1.5 wt%.

5. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, The two clamping members are connected, and the position of both clamping members relative to the main body is adjustable along the second direction.

6. The biodegradable magnesium metal artificial vertebral lamina according to claim 5, characterized in that, Both clamping members include connected adjustment sections and locking sections. One adjustment section is provided with a first rack, and the other adjustment section is provided with a second rack. The first rack has a plurality of first locking teeth arranged along the second direction, and the second rack has a plurality of second locking teeth arranged along the second direction. The first locking teeth at different positions can elastically engage with the second locking teeth at different positions. The two locking sections define the clamping cavity.

7. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, The main body is provided with an adjustment channel that extends through the main body along the second direction. Both clamping members include connected adjustment sections and locking sections. At least one of the two adjustment sections extends into the adjustment channel and its position relative to the adjustment channel along the second direction is adjustable. The two locking sections define the clamping cavity.

8. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, The bone contact surface of the protrusion is provided with a trabecular structure and / or a bone inlet hole.

9. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, Each of the mounting portions includes at least two lugs, the two lugs being spaced apart along the second direction and defining an opening slot, the lugs being provided with mounting holes, and the connector passing through the mounting holes; And / or, a bending groove is provided at the connection position between the mounting part and the main body, and the bending groove extends along the first direction; And / or, the main body is provided with a bone graft chamber.

10. The biodegradable magnesium metal artificial vertebral lamina according to claim 1, characterized in that, The mounting part is provided with a mounting hole, the connector is threaded into the mounting hole, the mounting hole is provided with a locking ring groove, and the outer peripheral wall of the connector is provided with a locking boss, which can be screwed into the locking ring groove.

11. The biodegradable magnesium metal artificial vertebral lamina according to claim 10, characterized in that, The front end of the locking boss is provided with a guide bevel so that it can be screwed into the locking ring groove; And / or, there are multiple locking bosses, and the multiple locking bosses are arranged at circumferential intervals along the locking ring groove.

Citation Information

Patent Citations

  • Spinous process vertebral plate replantation internal fixing device

    CN110141349A

  • Vertebral pars interarticularis clamp a new spine fixation device, instrumentation, and methodology

    US20110178552A1